Strategic information systems control practices in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management at Massey University - Eid, Mustafa Ismail Mustafa (Massey University, 2002)
A very important issue for companies is how well its Information Systems (IS) strategy supports its business strategy and direction. Strategic control of IS strategies is concerned with the monitoring, reviewing and maintenance of IS strategies from a strategic perspective, to ensure that IS strategies are performing well in terms of supporting the business strategy and direction in current and future business and information technology circumstances. The purpose of this study was to investigate strategic IS control practices of New Zealand organizations and to measure their level of effectiveness. A field survey of 123 New Zealand organizations provided the data for the study. The results show about 85% of NZ organizations practising IS planning also practice strategic oriented control over their IS plans, and with varying degrees of effectiveness. Three strategic IS control approaches have been identified: cybernetic, ad hoc, and a combined approach of both cybernetic and ad hoc. The cybernetic and combined approaches were found more than adequate, while the ad hoc is found to be just adequate. Strategic IS control is found to significantly influence the organizational IS plan performance. The study has identified five obstacles that work against the current practice of strategic IS control as follows (in order of significance): (1) lack of time, (2) lack of knowledge and/or expertise, (3) lack of tools, (4) difficulty of the task of strategic IS control, and (5) lack of funding. The variable industry competitiveness is found to be related to organizational intensity of IS use. The study also suggested further research recommendations to improve strategic IS control practice.
Keywords: Business strategy; Information technology; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management